The Effect of High Dosage of Iron Supplementation (Fe) Against Histopathology of Gastric Mucosa in Pregnant Strain Wistar White Rats (Rattus norvegicus) - Fatmawati Fatmawati; Dyah Aulia Perwitasari (Jurnal Indonesia Sosial Sains, 2023)
Pregnant women are encouraged to consume iron tablets during their pregnancy or at least 90 tablets during pregnancy. Side effects of iron tablets include nausea, vomiting, diarrhea, constipation. If the tablets is consumed in excess it will cause toxicity because excess iron will cause oxidative stress which can affect the state of the stomach. Purpose: to determine the effect of high-dose iron (Fe) supplementation on the histopathology of gastric mucosa in pregnant strain Wistar white rats (Rattus norvegicus). This study used 24 pregnant rats divided into 4 groups, that is, negative controls; treatment 1 with a dose of 0.54 mg; treatment 2 with a dose of 1.08 mg; and treatment 3 with a dose of 2.16 mg. Iron (Fe) supplementation was started from the 1st day of pregnancy until the 18th day, then on the 19th day the rats were dissected and the gastric organ was taken as a preparation with Hematoxylin Eosin (HE) staining and then observed with a light microscope. This study showed the histopathological results of gastric mucosa damaged in the treatment group which was assessed using the Barthel Manja score. The One Way ANOVA test results showed a significant difference from gastric mucosa (p = 0.000) in the control and treatment groups of this study. High doses of iron (Fe) supplementation affect the histopathology of gastric mucosa.